2020
DOI: 10.1111/ijpo.12609
|View full text |Cite
|
Sign up to set email alerts
|

Who benefits from the intervention? Correlates of successful BMI reduction in the Texas Childhood Obesity Demonstration Project (TX‐CORD)

Abstract: Background Many childhood obesity intervention studies report mean outcomes but do not explore the variation in responses and the characteristics of those who respond well. Objective To identify child and family characteristics associated with improvement in the primary outcome, %BMIp95, of the Texas Childhood Obesity Research Demonstration project (TX‐CORD). Methods The 12‐month TX‐CORD secondary prevention study randomized 549 children, ages 2 to 12 years, with BMI ≥85th percentile to the intensive intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In our study, those with severe obesity had the greatest magnitude of %BMIp95 reduction, which is promising in light of several previous studies that have shown greater effectiveness of behavioral obesity treatment interventions among youth with less-severe obesity/overweight; in some cases, children with severe obesity continued to gain weight [39][40][41]. These findings are particularly timely, as recent studies have shown that the greatest increase in childhood obesity prevalence has been observed in the severe-obesity category [1].…”
Section: Adaptations To the Bright Bodies Intervention Since 2007supporting
confidence: 74%
“…In our study, those with severe obesity had the greatest magnitude of %BMIp95 reduction, which is promising in light of several previous studies that have shown greater effectiveness of behavioral obesity treatment interventions among youth with less-severe obesity/overweight; in some cases, children with severe obesity continued to gain weight [39][40][41]. These findings are particularly timely, as recent studies have shown that the greatest increase in childhood obesity prevalence has been observed in the severe-obesity category [1].…”
Section: Adaptations To the Bright Bodies Intervention Since 2007supporting
confidence: 74%
“…In contrast, secondary prevention approaches focused on children who already have overweight and obesity and who need more aggressive behavioral strategies and guidance. Secondary prevention programs focused on individual families (10,24) and included at least 26 h of contact delivered in community settings, such as the YMCA (97).…”
Section: Using a Systems-level Approach To Address Childhood Obesity: Tx Cord Studymentioning
confidence: 99%
“…Furthermore, reflecting the broader literature and clinical guidelines, studies do not routinely differentiate between overweight, obesity, severe obesity and obesity with co‐morbidities, despite these conditions likely requiring differential management approaches. Clinical practice and research alike would benefit from more specific definitions, while recognising that individual presentations of obesity require personalised care based on clinical interpretation, accounting for adolescent growth trajectories, level of excess weight and possible co‐morbidities 28 …”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…To date, no one dietary approach has demonstrated superiority over another in the treatment of adolescent obesity or concomitant comorbidities. Data in children and adolescents have also shown individual variation in treatment response 27,28 . Hence, a range of dietary interventions are needed for adolescents with obesity.…”
Section: Introductionmentioning
confidence: 99%